2005
DOI: 10.1038/nature03331
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences between Saturn's ultraviolet aurorae and those of Earth and Jupiter

Abstract: It has often been stated that Saturn's magnetosphere and aurorae are intermediate between those of Earth, where the dominant processes are solar wind driven, and those of Jupiter, where processes are driven by a large source of internal plasma. But this view is based on information about Saturn that is far inferior to what is now available. Here we report ultraviolet images of Saturn, which, when combined with simultaneous Cassini measurements of the solar wind and Saturn kilometric radio emission, demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
161
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 17 publications
16
161
0
Order By: Relevance
“…In overall terms, observations show that the auroral brightness typically lies in the range ∼1-100 kR, while the total auroral output power generally varies from a few GW to a few tens of GW (Gérard et al, 1995Trauger et al, 1998;Cowley et al, 2004a;Clarke et al, 2005;Grodent et al, 2005;Badman et al, 2005). The values derived from our model lie in similar ranges, and are thus in basic accord with the observations.…”
Section: Auroral Parameterssupporting
confidence: 77%
“…In overall terms, observations show that the auroral brightness typically lies in the range ∼1-100 kR, while the total auroral output power generally varies from a few GW to a few tens of GW (Gérard et al, 1995Trauger et al, 1998;Cowley et al, 2004a;Clarke et al, 2005;Grodent et al, 2005;Badman et al, 2005). The values derived from our model lie in similar ranges, and are thus in basic accord with the observations.…”
Section: Auroral Parameterssupporting
confidence: 77%
“…5a (7 April at 06:26:11 UT) a latitudinally broad band of auroras spans from beyond the dawn meridian towards noon, extending poleward close to the magnetic/spin pole of the planet itself. Previous studies have shown that such "disturbed" auroral morphologies occur in response to rapid compressions of the magnetosphere by the solar wind Clarke et al, 2005Clarke et al, , 2009, possibly resulting in rapid reconnection and open-flux closure in the tail .…”
Section: Similarly Inmentioning
confidence: 99%
“…The XMM-Newton (3) observation (28 Oct. 2005, 06:34 to 29 Oct. 2005 was contemporaneus with three exposures of the Saturnian aurora taken with the HST Advanced Camera for Surveys, during a coordinated campaign with in-situ measurements by the Cassini spacecraft. This was a time of quiet solar wind conditions, and yet the UV aurora was seen to be very variable; the measured UV power at the time of the XMM-Newton observation varied between 3.3 and 8.0 GW Clarke et al (2005). (d) Bhardwaj et al (2007).…”
Section: The Origin Of the Rings X-ray Emissionmentioning
confidence: 99%